Maximizing Benefit and Minimizing Risk in Medical Imaging Use: An Educational Primer for Health Care Professions Students. (September 2018) - Armao, Diane; Hartman, Terry S; Shea, Christopher M; Katz, Laurence; Thurnes, Tracey; Smith, J Keith
"I am not young enough to know everything." Oscar Wilde Background: There is insufficient knowledge among providers and patients/caregivers of ionizing radiation exposure from medical imaging examinations. This study used a brief, interactive educational intervention targeting the topics of best imaging practices and radiation safety early in health professions students' training. The authors hypothesized that public health, medical, and physician assistant students who receive early education for imaging appropriateness and radiation safety will undergo a change in attitude and have increased awareness and knowledge of these topics. Materials and methods: The authors conducted a 1.5-hour interactive educational intervention focusing on medical imaging utilization and radiation safety. Students were presented with a pre/postquestionnaire and data were analyzed using t tests and multivariate analysis of variance. Results: A total of 301 students were enrolled in the study. There was 58% ( P < .01) and 85% ( P < .01) improvement in attitude and knowledge regarding appropriateness of imaging, respectively. The authors also found an 8% increase ( P < .01) in students who thought informed consent should be obtained prior to pediatric computed tomographic imaging. Physical assistant students were more likely than medical students to prefer obtaining informed consent at baseline ( P = .03). Conclusions: A brief educational session provided to health professions students early in their education showed an increased awareness and knowledge of the utility, limitations, and risks associated with medical imaging. Incorporation of a best imagining practice educational session early during medical education may promote more thoughtful imaging decisions for future medical providers.